Dampak Bullying pada Remaja Laki-laki Feminin: Studi Telaah Literatur - Zaidan, Abdullah; Yoenanto, Nono Hery (Buletin Riset Psikologi dan Kesehatan Mental, 2024)
Feminine men experience a lot of pressure from society, such as bullying and exclusion, in the hope that they will follow the prevailing gender norms. This becomes a pressure in itself and has an impact on their psychological dynamics. This article was written with the aim of studying the impact of bullying on feminine men. This article was prepared using the scoping review method based on previous research sourced from Google Scholar published between 2014 – 2023. The results of the analysis of 5 literature revealed that feminine men experience psychological impact on the emotional aspects: sense of insecurity, anxiety, feeling lonely, as well as feeling unhappy. Emotional aspects affect cognitive and behavioral aspects: decreased self-esteem, decreased academic ability, and decreased social functions such as helplessness, withdrawal and decreased social competence. The implications of the research are to build an inclusive environment, instill empathy and respect for differences, create anti-bullying programs and support victims of bullying.